Adherence at physical exercises in fitness centers Aderência à prática de exercícios físicos em academias de ginástica - De Liz C.M.* (2010)
The aim of this study is to investigate the reasons in the literature of adhesion and dropout of practitioners of physical exercises in fitness centers. This is a study of literature review with qualitative aspect. Using the descriptors in the health sciences to search for empirical studies in the databases available on the portal's regular Capes. Among the reasons mentioned for adhesion, it is the search for health, beauty, socialization, improving the physical condition and well-being. The dropout of fitness centers by practitioners of physical exercises has been attributed to lack of time, laziness, distance that the practitioner should go to their work or their home to the academy and the expensive price expend monthly. The identification and management of these factors should be considered in the promotion of physical activity and health.